Modelo de gestão em saúde: estudo de caso numa Entidade Confessional no Brasil - Bonicoski, Orival (Universidade do Vale do Rio dos Sinos, 2023)
This work evaluates the consequences of the process of changing from a health management model centered on treatment to a model centered on integration and prevention in a confessional entity in Brazil, where an integrated and preventive health management model framework was proposed. The study involved the participation of 174 people, including stakeholders, professionals and users, using a mixed, qualitative and quantitative methods approach. The following steps were carried out: step 1 document analysis, step 2 survey, step 3 focus group, step 4 interview and step 5 integrated analysis of data and recommendations. For quantitative data, SPSS® resources were used for descriptive statistical analysis and for qualitative data, Discursive Textual Analysis (ATD) was adopted, using NVivo 10® software. In the document analysis, the documents were classified according to the chronology of the implementation of the management model with their respective cycles: pre-implementation movements, implementation actions and maintenance procedures. In the perception of users, professionals and stakeholders, the current health management model is positive and the changes have brought assertive results. All stakeholders agreed that the health management model had a positive impact on the entity's financial health. Some challenges of the management model were also evaluated, such as regional, membership, financial, communication, sustainability and leadership, which could also be opportunities for the institution. Based on this study, managerial recommendations can be made to executives who manage health services aimed at aging groups. As it is limited to a specific time, the capacity to explore the field is a limitation of this study, which suggests the continuity of evaluations and the preservation of analysis of results with the maturation of the management model, and under conditions of growth in the number of people longlived in the confessional group studied. As a follow-up, future research can be explored for health management strategies in a long-lived religious population and extrapolated to the general population and a comparative analysis between different religious and long-lived populations.
Keywords: Modelo de gestão em saúde interdisciplinar; Entidade confessional; Modelo de gestão em saúde integrado e preventivo; Percepção em saúde de profissionais; Stakeholders; Usuários; Interdisciplinary health management model; Confessional entity; Integrated and preventive health management model; Health perception of professionals; Users; ACCNPQ::Ciências Sociais Aplicadas::Administração